OP0296 The risk of deliberate self-harm in rheumatoid arthritis and ankylosing spondylitis: a population-based cohort study. (12th June 2018) - Kuriya, B; Widdifield, J.; Luo, J.; Vigod, S.; Haroon, N.
Abstract : Background: Inflammatory arthritis is associated with the development of mental health disorders. However, there is limited data on the risk of serious mental health outcomes following a rheumatoid arthritis (RA) or ankylosing spondylitis (AS) diagnosis. Objectives: To estimate the risk of deliberate self-harm in patients with ankylosing spondylitis or rheumatoid arthritis compared with the general population. Methods: We evaluated population-based cohorts of RA (n=53, 240) and AS (n=13, 964), each matched 1:4 by age, sex, and calendar year (at diagnosis) with non-IA comparator cohorts in Ontario, Canada. Individuals with a history of mental illness or prior episode of deliberate self-harm were excluded. The outcome was a first emergency room presentation for deliberate self-harm, subsequent to RA or AS diagnosis, between April 1, 2002 and March 31, 2016. We estimated hazard ratios (HR) and 95% confidence intervals (95% CI) for RA and AS, separately, versus the comparator groups, adjusting for demographic, clinical and health service utilisation variables. Results: Individuals with AS were more likely to deliberately self-harm (incidence rate [IR] of 6.79/10, 000 person years [PY] compared to 3.19/10, 000 PY in comparators, with an adjusted HR 1.82 (95% CI: 1.26 to 2.62). Deliberate self-harm was also increased for individuals with RA (IR 3.51/10, 000 PY) compared to comparators (IR 2.45/10, 000 PY) only before (HR 1.43, 95% CI: 1.16 to 1.75), but not after covariate adjustment (HR 1.09, 95% CI: 0.88 to 1.36). The most frequent method of self-harm was poisoning (64% of attempts in AS, 81% in RA) or self-mutilation (36% in AS, 18% in RA). Conclusions: There is a significantly increased rate of self-harm attempt in inflammatory arthritis and the risk is particularly elevated following a diagnosis of AS. These findings highlight the need for routine evaluation of self-harm behaviour as part of the management of chronic inflammatory arthritis. Understanding the mechanisms contributing to deliberate self-harm attempts will help tailor preventive strategies to reduce morbidity associated with this serious mental health outcome. Acknowledgements: This work was funded by the Division of Rheumatology Pfizer Research Chair, University of Toronto Disclosure of Interest: None declared